Understanding Forfeitures An Analysis of the Relationship Between Case Details and Forfeiture Among TEOAF High-Forfeiture and Major Cases - Richardson, Amy (RAND Corporation, 2009)
The Treasury Executive Office for Asset Forfeiture (TEOAF) administers the Treasury Forfeiture Fund (TFF), which receives deposits of nontax forfeitures made by current and former Treasury agencies. Participating agencies use TFF funds to disrupt and dismantle criminal enterprises. This report examines the relationship between targeted funding support of major financial investigations and the forfeiture outcomes of such investigations.